Analysis of Porter's Five Forces on PT. Bank Rakyat Indonesia (Persero), Tbk - Juhari, Juhari; Anshori, Mochammad; Adriani, Nurita (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The aim of this research is to analyze Porter’s Five competitive force strategies of PT. Bank Rakyat Indonesia (Persero), Tbk. To compete in the banking industry. The research method used is a descriptive qualitative method. The data used is secondary data, with data collection using documentation data. From the results of research using five competitive forces PT. Bank Rakyat Indonesia (Persero), Tbk has a competitive advantage in the field of MSME credit, in lending. In 2022, BRI distributed credit amounting to 16.05% of total national credit. In maintaining this competitive advantage, BRI develops transformation strategies innovation in facing competition and change (adaptable). BRI provides digital services in banking activities, whether opening an account or making transactions using the Brimo application, even at the medium business or corporate level use the Business Internet Banking Application (Ibbiz) with more complete facilities.